Structural Effects of Calcium Depletion on the Manganese Cluster of Photosystem II: Determination by X-ray Absorption Spectroscopy - Latimer, Matthew J. (1998)
The structural consequences of calcium depletion of Photosystem II (PS II) by treatment at pH 3.0 in the presence of citrate has been determined by Mn K-edge X-ray absorption spectroscopy. X-ray absorption edge spectroscopy of Ca-depleted samples in the S(1)′, S(2)′, and S(3)′ oxidation states reveals that there is Mn oxidation on the S(1)′–S(2)′ transition, although no evidence of Mn oxidation was found for the S(2)′–S(3)′ transition. This result is in keeping with the results from EPR studies where it has been found that the species oxidized to give the S(3)′ broad radical signal found in Ca-depleted PS II is tyrosine Y(z). The S(2)′ state can be prepared by two methods: illumination followed by dark adaptation and illumination in the presence of DCMU to limit to one turnover. Illumination followed by dark adaptation was found to yield a lower Mn K-edge inflection-point energy than illumination with DCMU, indicating vulnerability to reduction of the Mn complex, even over the relatively short times used for dark adaptation (~15 min). EXAFS measurements of Ca-depleted samples in the three modified S states (referred to here as S′ states) reveals that the Fourier peak due to scatterers at ~3.3 Å from Mn is strongly diminished, consistent with our previous assignment of a Ca-scattering contribution at this distance. Even after Ca depletion, there is still significant amplitude in the third peak, further supporting our conclusions from earlier studies that the third peak in native samples is comprised of both Mn and Ca scattering. The Mn–Mn contributions making up the second Fourier peak at ~2.7 Å are largely undisturbed by Ca-depletion, but there is some evidence that S(1)′-state samples contain significant amounts of reduced Mn(II), which is then photooxidized in the preparation of higher S′ states.